A review of materials and their future development trends for lithium ion battery anodes. Issue 2 (July 2020) - Chen, Weichen
Abstract: With the development of electric vehicles and clean energy, the demand for lithium batteries as an important energy storage system has increased significantly in the past decades. Anode, an indispensable part in lithium batteries system, is currently mainly selected from carbon-based materials, silicon-based, tin-based alloys, and metallic lithium materials. Lithium battery with traditional carbon-based material can basically meet the requirements of most current consumer electronics products. Silicon-based and metallic lithium materials have greater development potential in terms of high energy density anode. This article introduces the carbon-based materials, silicon-based, metallic lithium materials and their common modification methods that have been widely studied at the current stage and discusses the future development trends of various anode materials.